1990
DOI: 10.2466/pms.70.3.883-888
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Dynamic, Static, and Rotary Balance of Deaf and Hearing Children

Abstract: The purpose of the present study was to measure the dynamic, static and rotary balance of deaf and hearing children. 20 deaf and 20 normal hearing students matched for mean age of 123 +/- 5.9 or 5.6 mo. and sex (11 boys, 9 girls) performed three tests of balance. A series of Wilcoxon signed-ranks tests and a Kendall Tau were applied to assess whether balance was affected in sensorineural deafness and to assess whether age and sex were factors in over-all balance, respectively. Significant differences were note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…In this study, deaf schoolchildren's performance in balance tests was mildly different from that of children with normal hearing, from a clinical point of view. However, this difference was not statistically significant and was not maintained when groups were compared on the basis of sex and age group, in common with findings reported by Gayle and Pohlman (17) . They investigated dynamic and static balance in 40 schoolchildren with a mean age of ten years (20 children with hearing loss and 20 children with normal hearing) and concluded that when age and sex were taken into account there were no differences between the two groups in terms of balance.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, deaf schoolchildren's performance in balance tests was mildly different from that of children with normal hearing, from a clinical point of view. However, this difference was not statistically significant and was not maintained when groups were compared on the basis of sex and age group, in common with findings reported by Gayle and Pohlman (17) . They investigated dynamic and static balance in 40 schoolchildren with a mean age of ten years (20 children with hearing loss and 20 children with normal hearing) and concluded that when age and sex were taken into account there were no differences between the two groups in terms of balance.…”
Section: Discussionsupporting
confidence: 86%
“…Contrary to this finding, Mann et al [31] in a previous study compared static and dynamic balance in 28 subjects who had peripheral vestibular disorders and found subjects with lesser degree of the handicap performed better than their counterparts who were more affected. Other investigators also found the lower level of dynamic balance among children with hearing impairment compared with the controls [13,21,[30][31][32][33]. Kegel et al [27] submitted that children with hearing impairments have a higher risk for deficits in balance and gross motor skills compared with children who are developing typically.…”
Section: Discussionmentioning
confidence: 94%
“…Os resultados deste estudo mostraram que não houve diferenças estatisticamente significativas nas comparações realizadas entre os gêneros quando os grupos foram analisados separadamente, logo, concordam com os estudos anteriores. (GAYLE et al, 1990).…”
Section: Discussionunclassified
“…da Educação Física/UEM Maringá, v. 21, n. 1, p. 47-57, 1. trim. 2010 Gayle et al, (1990), em um estudo realizado com 40 crianças (idade média de 10 anos) encontraram diferenças significativas no equilíbrio dinâmico de crianças com surdez neurossensorial comparadas com crianças ouvintes, sendo que estas últimas apresentaram um equilíbrio melhor. Este resultado reflete, provavelmente, que estas crianças surdas não aprenderam ainda a antecipar o desequilíbrio, que pode ocorrer durante o teste de equilíbrio dinâmico.…”
Section: Discussionunclassified